Sorption behavior of four tropical woods using a dynamic vapor sorption standard analysis system - Simo-Tagne, Merlin; Rémond, Romain; Rogaume, Yann; Zoulalian, André; Bonoma, Béguidé (Maderas. Ciencia y Tecnología, 2016)
Sorption behavior of four tropical woods coming from Cameroon is studied using a Dynamic Vapor Sorption-Intrinsic apparatus. Sorption isotherms at 20°C and 40°C of Triplochiton scleroxylon (obeche), Entandrophragma cylindricum (sapele), Sterculia rhinopetala (lotofa) and Terminalia superba (frake also called limba) are compared to those in the literature with methods using saturated salts for lotofa and frake with satisfactory results. Experimental values are fitted using two sorption isotherm models. Sorption hysteresis is greatest in sapele and least in frake. When temperature increases, differences in the hysteresis of sorption among the woods decreases. Hystereses of all studied woods ranged from 0,5 to 3%. Our studied woods have lower equilibrium moisture content probably caused by the higher values of extractives content. The water sorbed molecules on multilayer during both adsorption and desorption at 20°C and 40°C is greater in the case of frake and lower in the case of lotofa. The water sorbed molecules on multilayer of sapele is greater than those of obeche. The predominance of multilayer over monolayer of our woods is from 0,2 to 0,4 relative humidity in adsorption phase, and from 0,3 to 0,4 relative humidity in desorption phase.